2017
DOI: 10.1103/physrevlett.119.160401
|View full text |Cite
|
Sign up to set email alerts
|

Revealing Quantum Statistics with a Pair of Distant Atoms

Abstract: Quantum statistics have a profound impact on the properties of systems composed of identical particles. At the most elementary level, Bose and Fermi quantum statistics differ in the exchange phase, either 0 or π, which the wavefunction acquires when two identical particles are exchanged. In this Letter, we demonstrate that the exchange phase can be directly probed with a pair of massive particles by physically exchanging their positions. We present two protocols where the particles always remain spatially well… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
26
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 64 publications
0
26
0
Order By: Relevance
“…Formally, such coherences do not represent manipulable superpositions, but their presence in the steady state implies that the particles retain their capability to interfere (indistinguishability) in experiments of the Hong-Ou-Mandel type [48,49,52,53]. Indeed, it has been shown that superpositions originated from the exchange symmetry can become accessible and exploitable [48,[54][55][56][57].…”
Section: Discussionmentioning
confidence: 99%
“…Formally, such coherences do not represent manipulable superpositions, but their presence in the steady state implies that the particles retain their capability to interfere (indistinguishability) in experiments of the Hong-Ou-Mandel type [48,49,52,53]. Indeed, it has been shown that superpositions originated from the exchange symmetry can become accessible and exploitable [48,[54][55][56][57].…”
Section: Discussionmentioning
confidence: 99%
“…This fundamental question is, however, key to a variety of complex quantum phenomena, such as dynamical equilibration after a quench [34][35][36], correlation formation [37,38], or transport in interacting many-body systems [39,40]. Furthermore, certification of the bosonic, fermionic, as well as (in)distinguishable character of particles [12,14,[41][42][43][44] could also be achieved by identifying the corresponding interference fingerprints in the (interacting) dynamics.Hence, it is the purpose of this work to systematically explore the impact of particles' indistinguishability on the time evolution of interacting many-body systems. We consider bosons which occupy a discrete set of coupled modes and whose mutual (in)distinguishability is controlled by an additional internal degree of freedom.…”
mentioning
confidence: 99%
“…The energy spectrum of the angular momentum eigenstates is quadratic in quantum number, increasing the complexity possible in Hamiltonian engineering and enabling the simulation of rotational dynamics of diatomic molecules [4][5][6]. Moreover, the periodic boundary conditions of angular momentum states enable fundamentally new operations such as the deterministic coherent exchange of the ions' wave functions [7] and the ability to create interferometry geometries new to ions [8,9]. Rotational states also have fundamental physics applications in Aharanov-Bohm style experiments because of their enclosed area [10,11] and in observing Hawking radiation in acoustic analogs of black holes [12,13].…”
mentioning
confidence: 99%
“…For example, at a Ramsey time t revival = π ωr∆ , the phase of each superposition becomes an integer multiple of 2π, manifesting as a revival in the contrast of the excitation. Taking advantage of the symmetrization requirement to create a fully odd or even rotational mode occupation under particle exchange would induce an additional revival at t revival /2, which would demonstrate the indistiguishability of the two 40 Ca + ions even as they are separated by 6.27 µm at all times [7,26].…”
mentioning
confidence: 99%